Rancangan re-instalasi threshold light dan runway end light di bandar udara fransiskus xaverius seda maumere - Gusti Sectiorita Sipayung; Nurhedhi Desryanto; Ichyu machmiyana (Jurnal Pengetahuan dan Pendidikan, 2026)
The runway lighting system is a vital facility to ensure flight operational safety, especially at night or in low visibility conditions. This study aims to design the re-installation of threshold and runway end lights at Fransiskus Xaverius Seda Maumere Airport, transitioning from elevated to inset type with a 7-0-7 configuration on a 45-meter wide runway. The use of the inset type aims to create an obstacle-free zone at the runway threshold to minimize the risk of damage to aircraft tires and landing gear. The methodology employed is Research and Development (R&D) level 1, which includes field observations, interviews, and technical design. Load analysis results indicate a total circuit power requirement of 1.68 kVA, which is optimally served by a 4 kVA Constant Current Regulator (CCR) with an operational efficiency level of 42%. Geometric calculations resulted in a light spacing of 2.25 meters with an 18-meter center gap, complying with ICAO Annex 14 standards. Theoretical testing confirmed a voltage drop of 91.47 Volts, ensuring a stable distribution of the 6.6 Ampere current. The outputs of this research are Detailed Engineering Design (DED) and Bill of Quantity (BOQ) documents as technical references for the field implementation of the re-installation.